2013
DOI: 10.3389/fncel.2013.00130
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal cortex and temporal lobe epilepsy

Abstract: The perirhinal cortex-which is interconnected with several limbic structures and is intimately involved in learning and memory-plays major roles in pathological processes such as the kindling phenomenon of epileptogenesis and the spread of limbic seizures. Both features may be relevant to the pathophysiology of mesial temporal lobe epilepsy that represents the most refractory adult form of epilepsy with up to 30% of patients not achieving adequate seizure control. Compared to other limbic structures such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 87 publications
0
16
1
Order By: Relevance
“…Yet, a recent review of the literature [55] indicated a volumetric reduction of the perirhinal cortex in a subset of patients affected by temporal lobe epilepsy in spite of normal hippocampal volumes as well as a presence of selective neuronal loss and synaptic reorganization in the perirhinal cortex in the absence of hippocampal sclerosis. Interestingly, Guedj and colleagues [15] showed that performance on recognition tests in patients with temporal lobe epilepsy was correlated with interictal metabolism of entorhinal/perirhinal cortex but not with the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a recent review of the literature [55] indicated a volumetric reduction of the perirhinal cortex in a subset of patients affected by temporal lobe epilepsy in spite of normal hippocampal volumes as well as a presence of selective neuronal loss and synaptic reorganization in the perirhinal cortex in the absence of hippocampal sclerosis. Interestingly, Guedj and colleagues [15] showed that performance on recognition tests in patients with temporal lobe epilepsy was correlated with interictal metabolism of entorhinal/perirhinal cortex but not with the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Biagini et al, 2013), the onset of the ictal discharge recorded from the PC was charac-154 terized either by a series of 3-4 events that progressively increased in their rate of occurrence 155(Fig. 1Ca, arrows)or by a single, large amplitude transient (Fig.…”
mentioning
confidence: 99%
“…This disorder is characterized by irreversible biochemical and structural changes in the hippocampus and several neocortical regions [2][3][4]. In spite of the extensive research of last decades resulting in the discovery of new antiepileptic drugs available for clinical practice, up to 80 % of MTLE patients remain refractory to medication [5].…”
Section: Introductionmentioning
confidence: 99%